(untitled) (International Conference on Economics, Finance, Banking and Management, 2025)
Smart tourism, driven by technological advancements, is revolutionizing the way travelers experience destinations. This article explores the current state of smart tourism and the integration of smart technologies in Uzbekistan, offering a comparison with other global tourism hotspots. Using a comprehensive review of available data, this study highlights key innovations, challenges, and opportunities specific to Uzbekistan’s tourism sector. The findings suggest that while Uzbekistan is making significant strides in adopting smart technologies, it still lags behind other countries in certain areas, particularly in terms of infrastructure and widespread implementation.